COMPARATIVE STUDY OF MICROALBUMINURIA AND GLYCATED HEMOGLOBIN LEVELS IN TYPE 2 DIABETIC COMPLICATIONS - Mandal, Gunjan Kumar; D, Jyothrimayi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Microalbuminuria occurs when the kidney leaks a small amount of albumin into the urine or when there is an abnormally high permeability for albumin in the renal glomerulus. Microalbuminuria is a powerful risk factor of cardiovascular disease and for the presence and severity of diabetic retinopathy and neuropathy. The aim of this study is to compare the levels of microalbumin and glycated hemoglobin (HbA1c) levels in Type 2 diabetic complications. Methods: The study includes 100 patients with Type 2 diabetes mellitus visiting the diabetic out-patient department patients with complications, such as hypertension, retinopathy, neuropathy, and cardiovascular complication, was diagnosed based on history and clinical examination and related investigations. Microalbuminuria levels and HbA1c levels are compared in patients with complications (subjects) of Type 2 diabetes mellitus and patients without complications. Results: The study revealed that microalbumin levels are at a significantly higher range with high HbA1c levels in patients with complications (p<0.05). When compared to patients without complications. Conclusion: The study supports that strict glycemic control can prevent microalbuminuria and thereby prevent progress on to diabetic nephropathy in patients with Type 2 diabetes mellitus. Keywords: Microalbuminuria, Glycated hemoglobin, Diabetic complications